2018
DOI: 10.1108/ijmpb-10-2017-0118
|View full text |Cite
|
Sign up to set email alerts
|

Marketing for the project: project marketing by the contractor

Abstract: Purpose The purpose of this paper is to identify the marketing practices adopted by contractors in project-based industries to win new business and maintain relationships with existing clients. Design/methodology/approach The authors interviewed eight such contractors, and used activity theory as a lens to analyze the results. The authors investigated project marketing activities at four stages of the project contract life cycle, and against four enablers of collaboration. Findings The authors have identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…On the other hand, it was also used implicit attitude towards Project Marketing, which is defined by the authors of this study as the individual's unconscious assessment of the relationship between Marketing and Projects. This view follows another epistemological paradigm that proposes a reconciliation between marketing and PM [8], disregarded for some researchers in PM [43], but considered necessary for project-based organizations [59], being recently brought to discussion again [60]. We clarify that this view was measured unconsciously, using an instrument called project marketing IAT, that is, the Implicit Association Test for Project Marketing, based on the model of Greenwald, Mcghee, and Schwartz study [24].…”
Section: Procedures Scales and Techniquesmentioning
confidence: 90%
See 1 more Smart Citation
“…On the other hand, it was also used implicit attitude towards Project Marketing, which is defined by the authors of this study as the individual's unconscious assessment of the relationship between Marketing and Projects. This view follows another epistemological paradigm that proposes a reconciliation between marketing and PM [8], disregarded for some researchers in PM [43], but considered necessary for project-based organizations [59], being recently brought to discussion again [60]. We clarify that this view was measured unconsciously, using an instrument called project marketing IAT, that is, the Implicit Association Test for Project Marketing, based on the model of Greenwald, Mcghee, and Schwartz study [24].…”
Section: Procedures Scales and Techniquesmentioning
confidence: 90%
“…Cova, Ghauri, and Salle [9] point out that Project Marketing is a complex transaction covering a package of products, services, and labor, specially developed to create capital assets, which produce benefits for a buyer over an extended period. Turner, Lecoeuvre, and Sankaran [60] claim that Project Marketing considers marketing orientation and philosophy from the perspective of projects, including projects in a broader and business context. In this sense, we can argue that synergistically incorporating marketing assumptions into the project can contribute to success in PM.…”
Section: Project Management and Its Relationship With Marketingmentioning
confidence: 99%
“…Nobody cited the marketing literature on the topic, but several authors have written about relevant elements. Turner et al (2019) come the closest. They are talking about the interaction between the client and contractor from the contractor's perspective, but when talking about project marketing they suggest how the contractor can influence the client experience.…”
Section: Client Experience On Projectsmentioning
confidence: 98%
“…We saw above, that in retail Howard and Sheth (1969) suggested a three-stage customer journey. For projects, Lecoeuvre and Deshayes (2006) and Turner et al (2019) identified a four-stage cycle:…”
Section: The Journeymentioning
confidence: 99%
“…In line with the observations made by Cova and Salle (2000), informants argue that interpersonal practice has shifted in emphasis from transactional toward a wider span of activities. However, the transactional practice and bidding especially, still represent a major activity for many marketers operating in project business (Turner et al, 2018).…”
Section: Transactional Practicementioning
confidence: 99%